(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
To realize this editorial, years after the experience of founding this journal, demands of us a certain mnemonic work, since it is already 15 years of history since its origin. An ambiguous task, because it is somewhat herculean and at the same time, simple. Herculean by the mental effort with what to say now, having already spent so much time. But simple, for being a living history, the legitimate “mothers” of Estima. Thus, in thinking about the task, came from the tunnel of time a historical cadence: the idea, the exchange, the planning, the implantation and the celebration. Looking back, we were at the same time projected for the Now and the Future of this journal, which undoubtedly has fulfilled its mission within the Brazilian Stomatherapy and, why not, worldwide.